(untitled) (Journal of actual problems of jurisprudence, 2018)
This article defines the concept of threat in this criminal offense. The new legislation is considered a threat to our country – as a criminal offense, not a crime. The purpose of this article is to investigate the threats – both socially dangerous act. The features of the criminal liability of legal regulation of the threat of disclosing the concept of threat, as well as defining some aspects of criminal responsibility relevant to the enforcement activities. Key words: threat, offense, criminal offense, criminal code, responsibility, sanction.